2018
DOI: 10.29252/mlj.12.6.28
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Resistance Training with Blood Flow Restriction on Follistatin to Myostatin Ratio, Body Composition and Anaerobic Power of Trained-Volleyball Players

Abstract: Background and objectives: The present study was designed to determine the effect of blood flow restriction training (BFRT) on follistatin to myostatin ratio, body composition and anaerobic power of trained volleyball players. Methods: Eighteen trained volleyball players were randomly assigned into two study groups: resistance training with blood flow restriction (BFRT; n=9) and resistance training without blood flow restriction (WBFRT; n=9). The subjects performed trainings three sessions a week, for eight we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 32 publications
(28 reference statements)
4
13
0
Order By: Relevance
“…These regulatory markers have demonstrated an ability to either stimulate or inhibit muscular hypertrophy (1) . For instance, MSTN is recognised as a strong negative regulator of SMM, which acts by binding to activin type II receptors, eliciting an inhibitory response for muscle hypertrophy (30) . A previous investigation by Hulmi et al (23) demonstrated that following 21 weeks of RT, MSTN concentrations were only altered immediately postexercise in groups not consuming protein after the workout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These regulatory markers have demonstrated an ability to either stimulate or inhibit muscular hypertrophy (1) . For instance, MSTN is recognised as a strong negative regulator of SMM, which acts by binding to activin type II receptors, eliciting an inhibitory response for muscle hypertrophy (30) . A previous investigation by Hulmi et al (23) demonstrated that following 21 weeks of RT, MSTN concentrations were only altered immediately postexercise in groups not consuming protein after the workout.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TGF-β1 is known as a multifunctional protein that acts as a skeletal muscle regenerator since it contributes to extracellular matrix reconstitution as well as muscle tissue remodelling (33) . Several investigations have evaluated the aforementioned myokines to determine their role in RT-induced muscular adaptations (1,30,34,35) . Accordingly, we showed that 8 weeks of wholebody RT increased circulating FLST and decreased MSTN concentrations in middle-aged men (1) .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, blood flow restriction training (BFRT) with low intensities has been considered as an effective approach to increase SMM compared to traditional RT, which is performed with higher intensities (5). Recent studies reported a decrease in myostatin (MSTN) concentrations following RT (3,5). Blood flow restriction increases the muscle mass by regulating several cellular pathways, including the mechanistic target of rapamycin signaling, ribosomal protein S6 kinase beta-1 and forkhead box O (6).…”
Section: Introductionmentioning
confidence: 99%
“…This protein is produced in the skeletal muscle tissue and acts as a muscle growth inhibitor that circulates through the bloodstream and eventually binds to activing type II receptors (9). Evidence suggests that MSTN concentration decreases following eight weeks of RT with BFRT (7) or without BFRT (3,5,7). It has been suggested that RT could also reduce MSTN concentrations, resulting in increased SMM (9).…”
Section: Introductionmentioning
confidence: 99%
“…This means that training did not influence plasma myostatin in racehorses. In contrast, training of human and rat subjects generally led to a decrease in the serum/plasma myostatin concentration [49,[67][68][69]; however, a physical exercise intervention in recumbent patients resulted in an increase in this myokine [70]. In turn, de Souza et al [71] found no effect of different types of training on myostatin gene expression in muscles.…”
Section: Discussionmentioning
confidence: 98%